1999
DOI: 10.1115/1.2823513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Flatness Ratio of an Automotive Torque Converter on Hydrodynamic Performance

Abstract: Automotive torque converters have recently been designed with an increasingly narrower profile for the purpose of achieving a smaller axial size, which also translates into weight savings. Four torque converters with different flatness ratios were manufactured and tested in order to evaluate the change in their overall performance, including efficiency, stall torque ratio and torque transmission capacity. The experimental results show that the overall performance deteriorates when the flatness ratio is reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A number of researchers have studied the flat torque converter employing both analytical and experimental methods. Ejiri et al [11] manufactured and tested four torque converters with different flatness ratios. The experimental results show that the overall performance deteriorates when the flatness ratio is reduced to less than about 0.2.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have studied the flat torque converter employing both analytical and experimental methods. Ejiri et al [11] manufactured and tested four torque converters with different flatness ratios. The experimental results show that the overall performance deteriorates when the flatness ratio is reduced to less than about 0.2.…”
Section: Introductionmentioning
confidence: 99%
“…As the design of the torque converter tends toward flatter aspect ratios, the fluid motion may further aggravate blade loading and cracking. Ejiri and Kubo (1999) found that measured efficiency and torque capacity deteriorate with flatter designs. Corresponding numerical analysis indicated that a more pronounced jet-wake flow occurs at the pump exit with the flatter converter design, while efficiency loss at the pump inlet is attributed to an increased shock loss.…”
mentioning
confidence: 96%
“…Others have performed studies of the flow fields in torque converters, including Browarzik (1994), Ejiri and Kubo (1998), Marathe and Lakshminarayana (1997), and Watanabe and colleagues (1997). Efforts at the University of Virginia have used nonintrusive laser velocimetry to map out the detailed flow fields discussed by, for example, Brun and Flack (1994) and Whitehead (1995).…”
mentioning
confidence: 97%